1997
DOI: 10.18174/njas.v45i2.515
|View full text |Cite
|
Sign up to set email alerts
|

Non-overwintering cover crops: a significant source of N

Abstract: In field experiments in 1982-89 at 2 sites in the Netherlands, potatoes cv. Bintje and sugarbeet cv. Monohil or Ovatio in a wheat/potatoes/wheat/sugarbeet rotation were preceded during winter by fallow or a green manure crop of Lolium multiflorum cv. Tetila with 0 (G0), 100 (G100) or 200 kg N/ha (G200) or Trifolium pratense cv. Rotra with no N (RC). Green manure crops were undersown to winter wheat cv. Durin and ploughed in in the first half of November. On average, G0, G100, G200 and RC had then accumulated 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
2
7
0
2
Order By: Relevance
“…On the contrary, when no N fertilisation was given, the soil NO 3 -N at Laukaa in the last year of the experiment was lower after westerwold ryegrass than after no undersowing. This is in agreement with the findings of Schröder et al (1997), who reported that ploughing unfertilised Italian ryegrass immobilized soil mineral N.…”
Section: Discussionsupporting
confidence: 93%
“…On the contrary, when no N fertilisation was given, the soil NO 3 -N at Laukaa in the last year of the experiment was lower after westerwold ryegrass than after no undersowing. This is in agreement with the findings of Schröder et al (1997), who reported that ploughing unfertilised Italian ryegrass immobilized soil mineral N.…”
Section: Discussionsupporting
confidence: 93%
“…Apparent recovery of cover crop nitrogen (ANR) was calculated as suggested by Schröder et al (1997). ANR=100×false(NYccNYncfalse)/NYCC where NYcc = nitrogen yield of unfertilized crop preceded by cover crop, NYnc = nitrogen yield of unfertilized crop preceded by no‐cover crop, NYCC = aboveground nitrogen yield of the cover crop.…”
Section: Methodsmentioning
confidence: 99%
“…As for N, the "slow release" character of organic residues can be advantageous (e.g., under wet conditions, but can just as well contribute to an untimely mineralization followed by nitrate leaching losses). The consequent risks of these losses can only partly be compensated for by the establishment of cover crops (Schröder et al, 1996(Schröder et al, , 1997. As the kg's N per kg of phosphorus (P) in most organic residues are lower than the required ratio of N and P from the perspective of crop demand, too much P would be applied if input rates of (e.g., manures were tuned to the N demand of crops).…”
Section: Dilemmas Beyond the Primary Productivity Functionmentioning
confidence: 99%